If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+3)=-42
We move all terms to the left:
-2(x+3)-(-42)=0
We add all the numbers together, and all the variables
-2(x+3)+42=0
We multiply parentheses
-2x-6+42=0
We add all the numbers together, and all the variables
-2x+36=0
We move all terms containing x to the left, all other terms to the right
-2x=-36
x=-36/-2
x=+18
| -3x=x•-3 | | 5x-3(4-x)=20 | | 19x+6x=625 | | -2x^2+4x=10 | | 2x-7/8=3x+2/12 | | x+6+3=-5 | | x/3+5/2=x/6-3/2 | | 50=5x+25 | | 50x+12=2 | | y=10(1.04)5 | | -(z-14)=0 | | 45x+-15=-6 | | 5+10r=15 | | 13a-7=-7a+533 | | 8.8(x-1.750)=-17.6 | | 17x-5=180 | | 5=x÷3+7 | | 4r+-12=4 | | 17x-3+-17x+8=175 | | 10x+-12=-10 | | a-2a=-54 | | 5x-12=x+22 | | x/6+14=50 | | 0.10(50)+0.35x=0.05(x-16) | | (8r+3+3r)+(4r+6+2r)=6 | | -7(x-14)=84 | | 81=-3(x+7) | | 26.50+0.15c=14.50+0.25 | | -4x2+1=0 | | 2(h-5)=8 | | -4*k-(-4-3k)=-3k-2k-(3-6k0+1 | | 2x+6/4=4 |